Monte Carlo simulation of free radical production under keV photon irradiation of gold nanoparticle aqueous solution. Part II: Local primary chemical boost. (February 2021) - Poignant, Floriane; Charfi, Hela; Chan, Chen-Hui; Dumont, Elise; Loffreda, David; Gervais, Benoit; Beuve, Michaël
Abstract: For the past two decades, gold nanoparticles (GNPs) have been investigated as a radiosensitizing agent for radiation therapy. Many theoretical studies have shown that GNPs increase the dose deposition for keV photon irradiation, both at macro and nano-scales, due to a high photon-gold interaction probability. We studied by Monte Carlo simulations the production of radiolysis chemical products ( O H and H 2 O 2 ) following an ionization event induced by a 20–90 keV photon in a nanoparticle (NP). We focused here on the primary chemical processes occurring around nanoparticles. In the micrometer range, we obtained an excess of chemical species following GNP ionization, as compared to a reference water nanoparticle (WNP) ionization. This difference came from the dominant processes of photon interaction, i.e., Compton for water and photoelectric for gold, which are characterized by different emitted-electron energy spectra. The overproduction of chemical species could be up to 5 times higher for GNP, depending on the photon energy. The mean concentration of chemical species within 100 nm is higher for GNPs compared to WNPs due to Auger electrons when the nanoparticle radius was equal to 5 nm. On the contrary, it was quite comparable when the nanoparticle radius was equal to 50 nm. This reveals that gold Auger-electrons do not necessarily induce a significant boost of chemical species in the vicinity of GNP, as compared to WNP. However, the chance of GNP ionization to occur is larger, due to higher photon-gold interaction probability than that of water, and could result, especially for large GNPs, in accumulation of oxidative stress in its vicinity. Highlights: We calculated radical production around gold/water nanoparticle (GNP/WNP) in water. Calculations were performed for single keV photon absorption. In the micrometer range, radicals are overproduced by GNP compared to WNP. In the nanometer range, radicals are overproduced by small GNP compared to WNP due to Auger electrons. In the nanometer range, radical production is comparable for large NP.